Al-Ḥadāthah al-Islāmīyah al-mutaghayyirah: Ṣuwar li al-ṣūfīyah al-ḥaḍarīyah fī Indonesia wa Pakistan - Wardani, R. Yani'ah; Fadlan, Muhammad Nida' (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2021)
Over the last few decades, socio-religious changes in the middle-class Muslim community have transformed individual conceptions of what it means to be a ‘modern’ Muslim. It can be practiced even in conventional ways; joining a Sufi order (tarekat) group. This way refutes the perception of some groups who stigmatize Sufism as a ‘people’s religion,’ a form of rural religious practice. This article depicts Indonesia and Pakistan’s urban middle-class Muslim trend to practice the Qadiriyah tarekat. Although using the classical Sufism method, the middle-class Muslim in both countries still practice Sufism in a modern trend. This tarekat can facilitate the middle-class Muslim community to achieve a degree of ‘unity with God’ by using the tools of modernity. Besides its role as a medium for psychological therapy in the modern era, the Qadiriyah tarekat also contributes to various government programs, especially in anticipating humanitarian conflicts, preventing radicalism, strengthening harmony between communities, and initiating women’s empowerment movements.